Ethnicity and inclusion : religion, race, and whiteness in constructions of Jewish and Christian identities - Horrell, David G. (2020)
"A study of ethnic identity construction in Christianity and Judaism focused on New Testament texts"--
Includes bibliographical references and index.
Keywords: Identification (Religion) -- Biblical teaching; Identity (Psychology) -- Religious aspects; Christians; Jews in the New Testament; Ethnicity in the Bible; Racism -- Religious aspects